KEPENTINGAN INDONESIA EXIMBANK DALAM MENERIMA PINJAMAN DARI ICBC TIONGKOK TAHUN 2015 - Syafira An-nur; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia Eximbank join a partnership with ICBC Limited Tiongkok in 2015. The agreement between Indonesia Eximbank and ICBC Limited Tiongkok resulted in a loan of USD 500 Million and within a period of 5 years. The Indonesia government accepts it as financial capital for Indonesia Eximbank. Whereas, during 2015 Indonesia Eximbank showed good performance and gave recipients of PMN from the Indonesian government of 1 Trillion. This research describedabout Indonesia Eximbank received loans from ICBC Tiongkok.The qualitative research is Library research using data from books, journals, newspaper and using websites such as www.IndonesiaEximbank.go.id and www.icbc-ltd.com to describe Indonesia Eximbank partnership with ICBC Tiongkok. Nation-state level analysis with Liberalism perspectives about foreign loan theory was used to elaborate Indonesia Eximbank and ICBC Limited.The result showed that Indonesia Eximbank accept loan of USD 500 Million from ICBC Tiongkok in 2015 to strengthen if Indonesia Eximbank’s capital. Government programe of National Interest Area (NIA). Segment of export-oriented from UKM and support all the government’s export development program. Keywords: Indonesia Eximbank, ICBC Limited, Theory foreign Loans, Liberalism perspective.